2012
DOI: 10.1002/cjoc.201200978
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene Excimer‐based Bis‐triazolyl Pyranoglycoligands as Specific Mercury Sensors

Abstract: New C3,4‐disubstituted bis‐triazolyl glycoligands that feature a glucosyl or galactosyl scaffold incorporating two pyrenyl groups were synthesized via the CuI‐catalyzed azide‐alkyne 1,3‐dipolar cycloaddition reaction (Cue‐AAC). These compounds exert a major emission band corresponding to that of pyrene excimer and respond specifically to mercury with a markedly quenched fluorescence. The epimeric nature of the pyranoglycosyl scaffold is determined influential toward the selectivity of the sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…3,4-Bis-conjugation with pyrene moieties led to pyreneexcimer based bis-triazolyl glycoligands is for the selective detection of Hg 2+ in an aqueous solution. 212 Two glycoligands were prepared based on glucose and galactose respectively ( Figure 78) to investigate the 3,4-trans or 3,4-cis substitution pattern on the pyranose ring. Both the glycoligands could quench their fluorescence emission when Hg 2+ was added.…”
Section: Carbohydrate As a Core For One Or Multiple Fluorescent Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4-Bis-conjugation with pyrene moieties led to pyreneexcimer based bis-triazolyl glycoligands is for the selective detection of Hg 2+ in an aqueous solution. 212 Two glycoligands were prepared based on glucose and galactose respectively ( Figure 78) to investigate the 3,4-trans or 3,4-cis substitution pattern on the pyranose ring. Both the glycoligands could quench their fluorescence emission when Hg 2+ was added.…”
Section: Carbohydrate As a Core For One Or Multiple Fluorescent Dyesmentioning
confidence: 99%
“…Structures of the glucose-and galactose-based glycoligands for the detection of Hg 2+ . Reproduced from ref 212. with permission from the Wiley-VCH, copyright 2012.…”
mentioning
confidence: 99%
“… Examples of a saccharide modified pyrene derivatives. A pyrenyl β-cyclodextrin 38 by He et al [ 69 ], pyrenyl ( 39 ) and anthracenyl ( 40 ) glucose derivatives by Thakur et al [ 70 ] and glycoprobe by He et al [ 71 ]. …”
Section: Figurementioning
confidence: 99%
“…We recently reported that Cue-AAC is also a promisingly suitable tool for fabrication of FGs81524252627. By a twofold Cue-AAC between two azido fluorophores and a di-alkynyl glycoside, the resulting bis-triazolyl FGs exhibited distinct ion sensibilities in terms of the different fluorophores introduced10242526.…”
mentioning
confidence: 99%
“…The copper-catalyzed azide-alkyne 1,3-dipolar cycloaddition reaction (Cue-AAC) 18 19 20 , a prototype of the click chemistry 21 , has found wide applications in the construction of chemo-probes since the 1,4-disubstituted 1,2,3-triazole it forms represents a versatile ion coordination site 8 10 22 23 24 41 . We recently reported that Cue-AAC is also a promisingly suitable tool for fabrication of FGs 8 15 24 25 26 27 . By a twofold Cue-AAC between two azido fluorophores and a di-alkynyl glycoside, the resulting bis-triazolyl FGs exhibited distinct ion sensibilities in terms of the different fluorophores introduced 10 24 25 26 .…”
mentioning
confidence: 99%